CO-BEARING MINERALS IN ORES FROM THE MEDNORUDYANSKOE MALACHITE DEPOSIT (CENTRAL URALS) - V.I. Popova; V.A. Kotlyarov; V.A. Popov (Минералогия)
Cobaltite, Co-bearing pyrite, chalcopyrite and wad in ores from the Mednorudyanskoe deposit are characterized. Reserves of cobalt (about 3 000 t) were mainly concentrated in the Co-bearing hypogene minerals: pyrite and chalcopyrite with syngenetic intergrowths of cobaltite. Pyrite crystals are zonal by Co contents: up to 0.4 and 3.8–9.2 wt. % in the centre and periphery, respectively. Chalcopyrite contains 0.2–0.3 wt. % Co. Zonal micronodules of wad contains 5.15–10.88 wt. % CoO. Co-bearing pyrite and chalcopyrite from hypogene ores of the deposit are the source of Co for supergene minerals.